Identification of Differentially Expressed MicroRNAs in Osteosarcoma. (17th July 2011) - Lulla, Rishi R.; Costa, Fabricio F.; Bischof, Jared M.; Chou, Pauline M.; Bonaldo, Maria de F.; Vanin, Elio F.; Soares, Marcelo B.
Abstract : A limited number of reports have investigated the role of microRNAs in osteosarcoma. In this study, we performed miRNA expression profiling of osteosarcoma cell lines, tumor samples, and normal human osteoblasts. Twenty-two differentially expressed microRNAs were identified using high throughput real-time PCR analysis, and 4 (miR-135b, miR-150, miR-542-5p, and miR-652) were confirmed and validated in a different group of tumors. Both miR-135b and miR-150 have been previously shown to be important in cancer. We hypothesize that dysregulation of differentially expressed microRNAs may contribute to tumorigenesis. They might also represent molecular biomarkers or targets for drug development in osteosarcoma.